The I?BL gene polymorphism influences risk of acquiring systemic lupus erythematosus and Sjögren's syndrome (2008)
The human inhibitory ?B-like gene (I?BL) maps to a chromosomal region ?25 kb telomeric of the TNF gene at 6p21.3. I?BL encodes a protein related to I?B? that may interact with members of the NF-?B/Rel family. We evaluated the role of I?BL gene polymorphism in systemic lupus erythematosus (SLE) and primary Sjögren's syndrome (pSS). Genomic DNA isolated from individuals with SLE (n = 134), pSS (n = 67) and from individuals matched for age, sex, and ethnicity (n = 423) was genotyped for ?-473, -62T/A and +738T/C polymorphisms. The -62A allele was associated with a decrease in the risk of acquiring SLE in a recessive manner; whereas the +738C allele was associated with a more than twofold and threefold increase in the risk of SLE and pSS respectively, relative to the +738T allele. Four haplotypes were observed for the I?BL polymorphisms. Haplotype -62A+738T (AT) was associated with a 37% decrease in the risk of SLE, whereas AC tended to increase the risk of developing pSS. Using previously reported TNF data, an almost twofold increased in the risk of SLE was observed between haplotypes IKBL-62T+738T/TNF-308G-238G (TTGG) and TTAG because of linkage disequilibrium between IKBL-62T and TNF-308A. Our findings indicate that the I?BL gene influences the risk of developing SLE and pSS. © 2008 American Society for Histocompatibility and Immunogenetics.